The effect of environmental disclosure on stock return of Islamic and conventional banks - Widayanti, Mega Ayu; Rusgianto, Sulistya; Setianingsih, Hesti Eka; Kefeli, Zurina (Jurnal Ekonomi & Keuangan Islam, 2025)
Purpose – We examine the effects of environmental, social, and governance (ESG) disclosure and green building policies on the stock returns of Islamic and conventional banks. Methodology – Data were obtained from 17 Islamic banks and 17 conventional banks from eight countries (Arab Saudi Arabia, UAE, Qatar, Kuwait, Malaysia, Indonesia, Pakistan, and Bahrain) over seven years from 2017 to 2023. We conducted panel least squares with fixed effects (dummy variables) for cross-sections using EViews to process the data.Findings – The estimated results show that the green building policy variable is statistically significant to the stock return of Islamic banks, while the environmental, social, and governance variables are not. Meanwhile, the social dimension is statistically significant for the stock returns of conventional banks, but environmental, governance, and green buildings are not. Implications – Investors and policymakers should consider the implementation of ESG and green building policies to contribute on sustainability issues and gain financial return.Originality – This study tests non-financial performance, such as ESG disclosure and green building policy, on the stock returns of Islamic and conventional banks, which has not been extensively studied by the existing literature.